Peran Pemuda Dalam Menyongsong Hut Ri - Ulyatun Fatonah; Defi Safitri; Setia Wulan Dari; Lia Febrianti; Nabila Syam Jiwandini; Nur Reni; Eka Safitri (Universitas Ichsan Sidenreng Rappang, 2025)
Youth have a strategic role in welcoming the Republic of Indonesia's Anniversary (HUT RI), especially in maintaining and strengthening the spirit of nationalism and encouraging progressive social change. As agents of change, youth not only contribute to commemorating past struggles, but also face the challenges of globalization, technological advances and complex social problems. By taking advantage of opportunities such as digital technology and entrepreneurship, youth can play an important role in advancing the nation. Their active participation in the social, economic, political and educational fields is the key to realizing national ideals and maintaining national unity amidst global dynamics.